Evaluating the Effectiveness of Health Assistants in Facilitating Communication Between Patients and Healthcare Providers: A Qualitative Inquiry in Hafr Al-batin Hospitals - Mashari Abdullah A Alshammari; Fuhaid Ytaiym R Aldhafeeri; Abdulaziz Abdullah A Alshammari; Fahhad Yataim R Aldhafeeri; Ghanem Silfiq Duhaysan Aldhafeeri; Abdullah Shelaitan M Aldhafeeri (International Journal of Medical Toxicology and Legal Medicine, 2024)
Effective communication between patients and healthcare providers is essential for delivering high-quality care and improving patient outcomes. Health assistants play a crucial role in facilitating this communication, particularly in Saudi Arabian hospitals where language and cultural barriers may exist. This qualitative study aims to evaluate the effectiveness of health assistants in facilitating communication between patients and healthcare providers in Hafr Al-batin hospitals. Through semi-structured interviews with health assistants, patients, and healthcare providers, the study explores the perspectives and experiences of these stakeholders regarding the role of health assistants in enhancing communication and patient care. The findings reveal that health assistants contribute significantly to bridging communication gaps, providing language support, and assisting patients in navigating the healthcare system. However, challenges such as workload, limited training, and role ambiguity are identified as potential barriers to the effectiveness of health assistants. The study provides valuable insights into the importance of health assistants in facilitating communication and offers recommendations for healthcare organizations to optimize their roles and improve patient-provider communication in Saudi Arabian hospitals.